(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
This article examines the essence of commercial banks in order to understand the role of their activities in the economy and further development. The main operations available to all banks are considered. A number of features of commercial banks are given. The basics according to which the work of modern banks is carried out are presented. The functions of commercial banks that characterize their activities are analyzed in detail. The main conclusions of the work done are made.